Efficacy of Virtual Reality Distraction in Reduction of Pain and Anxiety of Pediatric Dental Patients in an Iranian Population: A Split-Mouth Randomized Crossover Clinical Trial - Zahra Bahrololoomi; Javad Zein Al-Din; Nahid Maghsoudi; Samira Sajedi (International Journal of Dentistry)
Background and Objectives. Dental fear and anxiety are common causes of dental care avoidance especially in pediatric dentistry. Distraction is among the safest and cheapest techniques for behavioral guidance in children. Virtual reality (VR) can be used as a means of distraction. This study aimed to assess the effect of distraction by VR on the levels of pain and anxiety in 6–8-year-old patients requiring mandibular primary molar pulpotomy. Materials and Methods. This crossover clinical trial was conducted with eligible 6–8-year-old children requiring bilateral mandibular molar pulpotomy. At the first treatment visit, pulpotomy was performed for 15 children using VR glasses distraction while the other 15 children received a pulpotomy without any VR glasses; this trend was reversed at the second session and pulpotomy was performed for the contralateral tooth. Pulse rate (PR) and Modified Child Dental Anxiety Scale (MCDAS) measured the anxiety levels. Wong–Baker Faces Pain Scale (WBFP) assessed the pain perception before and after the intervention. Data were analyzed by Statistical Package for the Social Sciences version 25 using the Mann–Whitney and χ2 tests. Results. The mean PR was not significantly different between the two groups. However, the test group showed significantly lower scores of MCDAS (P value = 0.02) and WBFP (P value = 0.001) compared with the control group. Conclusion. The present results suggest that VR headsets can decrease the level of pain and anxiety of patients during primary mandibular pulpotomy. This trial is registered with IRCT20200315046782N1.